Impact of risk stratification on the duration of caspofungin therapy for invasive fungal disease in acute leukemic patients. (February 2015) - Li, Wei; Zhao, Xingli; Gong, Benfa; Liu, Yuntao; Wei, Shuning; Zhang, Guangji; Liu, Kaiqi; Liu, Bingcheng; Wei, Hui; Wang, Ying; Lin, Dong; Mi, Yingchang; et al.
ABSTRACT : Aim: We retrospectively analyzed 141 acute leukemia patients with unclassified invasive fungal disease episodes during chemotherapy to determine the optimum duration of antifungal treatment.Patients & methods: Patients were divided into standard-risk and high-risk groups and treated with intravenous caspofungin for either 1 or 2 weeks, followed by oral voriconazole.Results: Favorable responses occurred in 75.9% of patients (107/141) overall. Although there were no significant differences in response rates between patients receiving 1 or 2 weeks in the standard-risk group (p = 0.12 and p = 0.19, respectively), in the high-risk group, response rates were significantly higher in the 2-week than the 1-week treatment group (p = 0.01 and p = 0.02, respectively).Conclusion: The duration of caspofungin treatment for patients with unclassified invasive fungal diseases may be optimized by risk stratification.